2019
DOI: 10.14359/51716834
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Resistance to Monitor Carbonation and Chloride Ingress

Abstract: He has published numerous papers on in situ measurement of transport properties of concrete and alkali activated cementitious materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…A similar behavior between zero and seven days has been described by Wang et al [41], who observed that the resistivity does not decrease instantaneously with the ingress of Cl − because there is no contribution to the electric current flow at the moment of chloride ion binding to the hydration products. Similarly, Loche et al [42] reported that Cl − ions modified the electrical response of cement-based materials.…”
Section: Electrical Resistivity Of Chloride-free Specimenssupporting
confidence: 82%
“…A similar behavior between zero and seven days has been described by Wang et al [41], who observed that the resistivity does not decrease instantaneously with the ingress of Cl − because there is no contribution to the electric current flow at the moment of chloride ion binding to the hydration products. Similarly, Loche et al [42] reported that Cl − ions modified the electrical response of cement-based materials.…”
Section: Electrical Resistivity Of Chloride-free Specimenssupporting
confidence: 82%
“…Determination of electrical resistivity is also a standardized method for investigating properties of hardened concrete (EN-12390-19) [16]. The application of this technique as a qualitative way for better understanding of the hydration evolution in cementitious matrices [17,18] as well monitoring durability of concrete [19][20][21], is discussed in the literature. However, up to the knowledge of the authors no record of using this technique to monitor carbonation profiles in cementitious specimens is reported in the literature.…”
Section: Introductionmentioning
confidence: 99%